Latin America and Third-Worldism in the Media - Barrera Rivera, Abner (2020)
This article is an analysis of interviews carried out by journalists from different media from The United States, Great Britain, Peru and Costa Rica to Rafael Correa while he was still president of Ecuador. The interviews address the topics of Human rights, democracy, and presidential reelection, Latina America, Cuba, the United States, Press Freedom and the OEA. In each of these interviews, former president Rafael Correa questions the perspectives and approaches of the interviewers on America Latina. From this exchange of opinions with his Interviewers, Correa makes his own analysis and shows that the mass media there represented, express their visions and perspectives on the progressive governments of America Latina which he considers to be ethnocentric, neo colonialist and third world visions. In conclusion, the ideas here developed by the interviewee in regards to the visions of the journalists, contain persuasive historical, political, social and cultural reasoning, which render the Journalists with no proper reasoning.